Pengaruh pH dan Kecepatan Pengadukan terhadap Penyerapan Zat Warna Methylene Blue menggunakan Biosorben Kulit Langsat (Lansium domesticum) Termodifikasi Cetyltrimethylammonium Bromide (CTAB) - Najwa Annisa Oktaviana; Desy Kurniawati (Lembaga Yasin AlSys, 2025)
Textile dye waste such as Methylene Blue is a hazardous pollutant that is difficult to degrade, thus requiring environmentally friendly treatment solutions. This study aims to utilize langsat peel waste (Lansium domesticum) modified with the cationic surfactant Cetyltrimethylammonium Bromide (CTAB) as a low-cost biosorbent for the removal of Methylene Blue, with a focus on improving adsorption capacity and examining the effects of process variables, namely pH and stirring speed. The langsat peel was prepared, ground to a particle size of 150 µm, and modified with CTAB. Batch adsorption experiments were conducted by varying the pH (2–10) and stirring speed (100–300 rpm). The concentration of Methylene Blue was analyzed using a UV-Vis spectrophotometer. The results showed that the optimal adsorption occurred at pH 6 with a capacity of 5.57 mg/g, while the optimal stirring speed was 200 rpm, yielding the highest adsorption capacity of 17.9 mg/g. These findings demonstrate that CTAB-modified langsat peel significantly enhances its effectiveness as a potential biosorbent for the remediation of Methylene Blue-containing wastewater.